1999
DOI: 10.1002/j.1550-8528.1999.tb00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat, Resting and Exercise Blood Pressure and the Angiotensinogen M235T Polymorphism: The Heritage Family Study

Abstract: . Body fat, resting and exercise blood pressure and the angiotensinogen M235T polymorphism: the Heritage family study. Obes Res. 1999;7:423- 430.Objective: The association of resting and exercise blood pressure (BP) and fat mass with the angiotensinogen (AGT) M235T polymorphism was investigated in 522 sedentary Caucasian subjects from 99 families. Research Methods and Procedures:Resting BP was measured on two separate days, three times each day, and the mean of six valid measurements was used. Exercise BP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…The increased expression of AGT is an important characteristic of preadipocyte differentiation, especially because Ang II has a fundamental role in this process. It was previously demonstrated that AGT expression is elevated in obesity (20,21). Zucker rats show an increased expression and secretion of AGT in adipocytes (22).…”
Section: Discussionmentioning
confidence: 97%
“…The increased expression of AGT is an important characteristic of preadipocyte differentiation, especially because Ang II has a fundamental role in this process. It was previously demonstrated that AGT expression is elevated in obesity (20,21). Zucker rats show an increased expression and secretion of AGT in adipocytes (22).…”
Section: Discussionmentioning
confidence: 97%
“…33 Others also have reported interactions between body fat, blood pressure, and AGT genotype. 34 The lack of sympathetic nervous system effects on adrenal aldosterone production may explain the absence of an association between BMI and adrenal response. Although multiple factors affected renal vascular response, AGT genotype and sex were associated primarily with adrenal response in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the HERITAGE Family Study, resting blood pressures were measured using Colin STBP-780 automated units (San Antonio, TX, USA) and the recordings were confirmed by technicians wearing ear phones. 20,38 Resting blood pressure was obtained on two separate days before 11:00 am in the post-absorptive state and with no caffeine-containing beverages or tobacco products for at least 2 h before assessment. Measurements were performed in a quiet room at neutral ambient temperature (24 -25 C) with the lights dimmed.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%